Family time use and home learning during the COVID-19 lockdown - Alison Andrew; Sarah Cattan; Mónica Costa Dias; Christine Farquharson; Lucy Kraftman; Sonya Krutikova; Angus Phimister; Almudena Sevilla (Institute for Fiscal Studies (IFS), 2020)
The COVID-19 school closures forced children and parents to make unprecedented changes to their daily routines. Including the summer holidays, most children will have had a five-and-a-half-month break from physically attending school by the time they returned in September. There has been considerable discussion of the challenges that home learning presents for some children, and the inequalities that it could lead to (Burgess and Vignoles, 2020; Education Endowment Foundation, 2020; Eyles, Gibbons and Montebruno, 2020). In this report, we present analysis of some of the first data on children's lives during the lockdown and how home learning during the lockdown worked in practice. Between 29 April and 20 June 2020, we interviewed over 5,500 parents with at least one child entering Reception in September 2020 or a child in school aged 4-15. We asked parents about their employment circumstances, as well as how they and their children spent their time during a weekday. We also asked about the resources (both from their schools and at home) that school-age children had available for home learning. We collaborated with an online survey company to ensure that our respondents came from a mix of genders, regions, and social and economic backgrounds. We then reweighted our data to ensure that they are as representative as possible of families with school-aged children in England.
Keywords: 330; Schüler; Unterricht; Lernen; Familie-Beruf; Coronavirus; England